Project Scheduling Management in the Software Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Project scheduling is the next step once project planning is completed. This requires knowledge and the depth of the activities, the dependencies between activities and, duration of the activities. Creating and designing a realistic project schedule is the biggest challenges a project manager faces. There are some common problems that can be impact towards project delay or performance: Assigning Resource or Resource Constraint, Managing the Unknown or Managing Change and Estimating Task Duration. These 3 factors and causes are contributing to project scheduling problem. The impact of resource constraint causes towards be impact towards project delay or performance.  To achieve this goal, the survey has been conducted. Finally, the results of the surveys are presented in order to see which commons problems are the most happening and really effected project scheduling.